Zero returns to compulsory schooling in Germany: evidence and interpretation - Jörn-Steffen Pischke; Till von Wachter (Institute for the Study of Labor (IZA), 2005)
We estimate the impact of compulsory schooling on earnings using the changes in compulsory schooling laws for secondary schools in West German states during the period from 1948 to 1970. While our research design is very similar to studies for various other countries, we find very different estimates of the returns. Most estimates in the literature indicate returns in the range of 10 to 15 percent. We find no return to compulsory schooling in Germany in terms of higher wages. We investigate whether this is due to labor market institutions or the existence of the apprenticeship training system in Germany, but find no evidence for these explanations. We conjecture that the result might be due to the fact that the basic skills most relevant for the labor market are learned earlier in Germany than in other countries.
Keywords: I21; J24; J31; 330; human capital; returns to schooling; school leaving age; ability bias; Allgemeinbildende Schule; Bildungsertrag; Humankapital; Schätzung; Deutschland